Translation of Owabong Waterpark Website from Indonesian into English - Muhammad Naufal Fikri (Jurnal Vokasia, 2024)
This article is entitled "Translating Owabong Waterpark Website from Indonesian to English" with the aim of translating the information content on Owabong website. Data was collected through observation, interview with Owabong marketing manager, documentation from the website, and hands-on practice looking for references from similar sites. The data was then translated, edited and added back to the website to ensure accuracy and relevance. Translation techniques used included literal translation and pure borrowing. The results were discussed with Owabong supervisors and management and added as a new feature on the website, easing access to information for foreign visitors and strengthening Owabong's international image as a tourist destination.